2012
DOI: 10.1007/s11999-012-2247-1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Impairment After Surgically Treated Lateral Compression Pelvic Injury

Abstract: Background Recently, fixation of lateral compression (LC) pelvic fractures has been advocated to improve patient comfort and to allow earlier mobilization without loss of reduction, thus minimizing adverse systemic effects. However, the degree of acceptable deformity and persistence of disability are unclear. Questions/purposes We determined if (1) injury pattern; (2) demographics; (3) final posterior displacement; (4) L5/ S1 involvement; (5) associated injuries; and (6) time influence outcome measurements, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…There are many causes for pain in a polytraumatized patient. Interestingly, Hoffman et al [12] found polytraumatized patients had lower pain scores at 6 months than their counterparts with isolated pelvic fracture. We anticipated difficulty delineating which effect the pelvic injury has relative to the whole picture, but we designed a pragmatic trial to include polytraumatized patients in our study because it is more reflective of our patient population and is part of our daily clinical decision-making, therefore making our findings more generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…There are many causes for pain in a polytraumatized patient. Interestingly, Hoffman et al [12] found polytraumatized patients had lower pain scores at 6 months than their counterparts with isolated pelvic fracture. We anticipated difficulty delineating which effect the pelvic injury has relative to the whole picture, but we designed a pragmatic trial to include polytraumatized patients in our study because it is more reflective of our patient population and is part of our daily clinical decision-making, therefore making our findings more generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies excluded patients who could not complete questionnaires or participate in the follow‐up, likely excluding head injured patients from their studies, and reducing the generalizability of their results. Disentangling disability associated with pelvic fracture from disability associated with other sustained injuries is challenging . We used a functional outcome instrument recommended for multi‐trauma populations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sagi et al [7] proposed a modification of the Young and Burgess classification system for LC-1 injuries, into LC-1a (not requiring surgical treatment) and LC-1b (may require surgical treatment), based on the amount of displacement during MUA which showed that almost 40 % of LC-1 injuries are inherently unstable. The MUA was also used in a recent study to test the stability and guide the treatment of Tile Type-B fractures of the pelvis [26]. Despite the above data, there is still a debate as to whether there is a clear indication for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%